Quill.org in the Post-Task Phase of TBLT: A Quasi-Experimental Study on EFL Learners’ Mastery of Simple Sentences - Ardini, Dessy Ayu; Rahmasari, Annisa; Andanty, Ferra Dian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Quill.org is an interactive online web for grammar exercises tool that is believed can helped the students master grammar well. This study observed the effect of Quill.org as a tool in Task-Based Language Teaching to enhance students’ simple sentence mastery for creating descriptive writing. Two classes underwent a three-session descriptive text writing unit using a quasi-experimental pretest–posttest control group design. While the control group received conventional training, the experimental group used Quill.org. Writing samples were used to assess sentence completeness, grammatical accuracy, and structural clarity. The findings showed that students in the experimental group produced grammatically correct short sentences at a statistically significant increase (p < 0.01), and that learners' opinions of Quill.org were favorable, describing it as helpful and boosting confidence. The results demonstrate the advantages of using specially designed digital resources into writing instruction to support student confidence, accuracy, and clarity in EFL contexts.